KOMUNIKASI ANTARPRIBADI PETUGAS LEMBAGA PEMASYARAKATAN DALAM MEMBINA NARAPIDANA NARKOBA - Maini Sartika; Mita Fitrati; Nur Anisah; Nadia Muharman (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
This research was conducted to find out the interpersonal communication of Banda Aceh Class IIA Prison Officers in Fostering Drug Prisoners and what are the supporting factors and inhibiting factors. The method used is the Qualitative Method, which is researching in depth with data collection techniques such as observation, interviews and documentation. This research used  Social Penetration theory, a process of relationship with others, where there are various adaptation processes between the two. The results of his research, the implementation of fostering prisoners with interpersonal communication approach in Class IIA Penitentiary Banda Aceh has been running as it should because the training carried out has followed existing procedures, although there are things that occur in prisons such as prisoners' indiscipline then that can be resolved with wise. Interpersonal communication in the coaching process that is carried out is also very appropriate, because a good coaching is also good communication. In conducting a coaching program, Banda Aceh Class IIA Prison certainly has supporting factors in the form of an adequate budget and the enthusiastic participation of fostered citizens in participating in coaching activities. There are also inhibiting factors, namely the lack of discipline from prisoners in carrying out training programs and the lack of prison staff.